Pengaruh Ketidakpuasan, Variety Seeking Dan Kualitas Jaringan Provider Terhadap Perpindahan Merek Kartu Prabayar Lain Ke Kartu Prabayar Telkomsel Pada Mahasiswa Unisma - Maulana, Nur Muhammad Afif; Rachma, N.; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2025)
Abstract As prepaid card users, unisma students have a phenomenon that is very responsive to the quality of services they receive. They tend to decide to switch brands from the experience of dissatisfaction with previous cards, the quality of the provider's network and the variety of products that satisfy users. Therefore, Telkomsel service providers must consider these factors to retain and attract new customers, especially in the student segment. The purpose of this study is to analyze the influence of dissatisfaction, variety seeking and provider network quality on the transfer of other prepaid card brands to Telkomsel prepaid cards in unisma students, both simultaneously and partially. The type of research used is (explanatory research) using a quantitative approach method with purposive sampling techniques on 85 respondents. The instrument used in this study is a questionnaire with a Likert scale that offers five answer options. The validity test was tested by calculating the value of the pearson correlation and comparing it with the value of the r-table of the table. Meanwhile, the realism was tested using Cronbach's alpha formula and the hypothesis was tested through multiple linear regression. Based on the results of the study, it was found that each independent variable had a positive and significant effect partially and simultaneously on the dependent variable. This study also found that the coefficient of determination (R) was 0.467 and the coefficient of α determination was 0.533. This shows that the independent variables consisting of dissatisfaction, variety seeking and provider network quality have a fairly good ability to explain their influence on the transfer of other prepaid card brands to prepaid cards. Keywords: Dissatisfaction, Variety Seeking, Provider Network Quality and Brand Displacement.